1995
DOI: 10.1002/jca.2920100404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type of exchange fluid on survival in therapeutic apheresis for thrombotic thrombocytopenic purpura

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a potentially lethal disease that may respond favorably to plasma infusion or therapeutic plasma exchange (TPE) with frozen plasma (FP) as the exchange fluid. Frozen plasma from which the cryo-precipitated fraction has been removed (cryopoor plasma, CP) has reportedly been useful in refractory cases in which a response to FP is not being observed. We report a retrospective analysis of all cases of TTP treated by TPE with either FP (1985-1989) or CP (1989-1993) as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Plasma exchange with CPP has been used when patients responded incompletely to FFP, and subsequent responses were attributed to a greater efficacy of CPP [11,12]. Other retrospective, uncontrolled studies have suggested an improved response rate and survival in newly diagnosed patients with TTP [13,14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Plasma exchange with CPP has been used when patients responded incompletely to FFP, and subsequent responses were attributed to a greater efficacy of CPP [11,12]. Other retrospective, uncontrolled studies have suggested an improved response rate and survival in newly diagnosed patients with TTP [13,14].…”
Section: Discussionmentioning
confidence: 96%
“…Cryoprecipitate poor plasma (CPP) has been suggested as a preferable exchange fluid because of the contributory role of vWF in the pathogenesis of TTP [5][6][7][8][9], the reported effectiveness of CPP as salvage therapy for refractory TTP [11,12] and the suggestion of its superiority in non-randomized studies in the treatment of TTP [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…With CSP, there was some decrease in the quantity of vWF after therapy. A retrospective analysis by Owens (Owens et al, 1995) also compared patient survival following the use of either FFP or CSP. The survival was 72% in the group that received CSP and 47% in the group which received FFP.…”
Section: The Syndromementioning
confidence: 99%
“…At this time, there are only two studies that have evaluated its use in this manner. 6,40 One study compared patient survival at a large tertiary‐care hospital using either CRP or FFP as replacement fluid in plasma exchange procedures. 40 From 1985 to 1989, 19 patients were treated with FFP.…”
Section: Crp In the Treatment Of Ttpmentioning
confidence: 99%